Regular exercise reduces the risk of all-cause mortality in socially isolated older adults: the Otassha Study - Ejiri, Manami; Kawai, Hisashi; Imamura, Keigo; Fujiwara, Yoshinori; Ihara, Kazushige; Hirano, Hirohiko; Obuchi, Shuichi (Frontiers in Public Health, 2024)
Introduction: Social isolation is associated with increased mortality risk. On the other hand, some older adults prefer to be alone. Additionally, predictors of isolation are mostly unchanged across interventions. Therefore, knowledge of how to prevent negative health outcomes in isolation would be beneficial. One of the factors that reduces the risk of mortality is regular exercise. However, to date, no studies to our knowledge have examined whether regular exercise reduces mortality among socially isolated individuals. This study aimed to determine the effects of the combination of social isolation and regular exercise on mortality among community-dwelling older adults. Methods: This prospective cohort study was part of the larger Otassha Study of community-dwelling older adults living in Itabashi Ward, Tokyo, Japan. In October 2012, 835 individuals (males=350, females=485; mean age 73.1 years) completed a comprehensive baseline health survey. Individuals were considered socially isolated if their frequency of interactions with others averaged less than once per week. Regular exercise was defined as exercise performed at least twice a week. The participants were assigned to one of the following four groups: 1) not isolated with regular exercise, 2) not isolated without regular exercise, 3) isolated with regular exercise, and 4) isolated without regular exercise. All-cause mortality information was obtained from the ward office database. Follow-ups were conducted until November 1, 2020. A Cox proportional regression analysis was performed. Results: A final analysis was performed on a complete dataset of 735 participants (males=303, females=432; mean age 72.9 years). A total of 132 (18.0%), 426 (58.0%), 27 (3.7%), and 150 (20.4%) participants were assigned to groups 1, 2, 3, and 4, respectively. The mortality rates in groups 1, 2, 3, and 4 were 6.1%, 9.2%, 7.4%, and 19.3%, respectively. Compared with group 1, isolated individuals who did not perform regular exercise had a significantly higher mortality rate (adjusted hazard ratio [aHR], 2.48; 95% confidence interval [CI], 1.12-5.52). However, no significant association was noted in isolated individuals who performed regular exercise (aHR, 1.25;95% CI, 0.26–5.91). Conclusions: Regular exercise was associated with a decrease in mortality risk, regardless of social isolation status.